2016
DOI: 10.1007/s11764-016-0574-z
|View full text |Cite
|
Sign up to set email alerts
|

Non-graduation after comprehensive school, and early retirement but not unemployment are prominent in childhood cancer survivors—a Finnish registry-based study

Abstract: Reassuring is that premature retirement was less common during the most recent treatment era. Screening and follow-up of psychosocial performance more effectively might be essential, and there is a need for studies on possibility for effective rehabilitation of the survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
59
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(71 citation statements)
references
References 46 publications
8
59
3
1
Order By: Relevance
“…However, in the present study, as well as in a study of childhood cancer survivors, including several diagnoses (Ahomaki et al, 2017), a statistically significant higher proportion of survivors were on sick leave or disability pension compared to non-cancer groups. However, in the present study, as well as in a study of childhood cancer survivors, including several diagnoses (Ahomaki et al, 2017), a statistically significant higher proportion of survivors were on sick leave or disability pension compared to non-cancer groups.…”
Section: Discussioncontrasting
confidence: 65%
“…However, in the present study, as well as in a study of childhood cancer survivors, including several diagnoses (Ahomaki et al, 2017), a statistically significant higher proportion of survivors were on sick leave or disability pension compared to non-cancer groups. However, in the present study, as well as in a study of childhood cancer survivors, including several diagnoses (Ahomaki et al, 2017), a statistically significant higher proportion of survivors were on sick leave or disability pension compared to non-cancer groups.…”
Section: Discussioncontrasting
confidence: 65%
“…Studies of the employment status of survivors of a broad range of childhood cancers in comparison with the general population or sibling comparisons had inconsistent findings . Seven studies observed higher unemployment rates among survivors, whereas five studies found similar unemployment rates . Studies with stratification by type of unemployment found that survivors were more likely to be unemployed due to illness or disability .…”
Section: Resultsmentioning
confidence: 95%
“…Many studies found that survivors of a CNS tumour achieved a much lower educational level than an external group without a history of childhood cancer or than survivors of other types of childhood cancer . Additional determinants identified across the studies included treatment with radiation therapy (most frequently CRT) and younger age at diagnosis …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations